Analisis Kinerja Protokol Routing Fisheye State Routing (FSR) dan Dynamic Source Routing (DSR) pada Mobile Ad-Hoc Network (MANET) - M. Fatkur Rohman; Heru Nurwarsito (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
MANET has 2 main types of routing protocols, namely reactive routing protocol and proactive routing protocol. One example of a reactive protocol is DSR (Dynamic Source Routing) and the proactive protocol is FSR (Fisheye State Routing). Mechanisms differ in communication, so the performance of the two routing protocols is different. The node route is so dynamic at any point in time, it can change and become one of the factors in the performance of the MANET routing protocol. In this study using DSR and FSR protocols because each type of routing protocol has a different algorithm significant impact on the performance of routing protocols in topology. MANET uses Network Simulator 2.35 with parameters End to End Delay, Routing Overhead, Packet Delivery Ratio and Thoughtput. The test scenario was carried out with variations in the number of nodes of 10, 25, 50, 75 and 100 nodes, and with variations in package sizes of 512, 1024 and 2048 bytes, and with speed variations of 5 m/s, 10 m/s and 15 m/s. The result is an average end-to-end delay based on the number of nodes, package size and node speed lower than the FSR protocol with an average value of 3.74 s, 5.32 s and 25.32 s. While with the average value of DSR protocol is 2.06 s, 3.08 s, and 72.27 s. For overhead routing tested based on number of nodes, package size and node speed are lower with an average value of 854.85 packets, 519.06 packages and 836.76 FSR protocol packages, while with an average value the DSR protocol is 61.02 packages, 36.15 packages and 153.6468 packages. Packet delivery ratio tested based on number of nodes, data package size and node speed are higher than FSR protocol with average values of 48%, 39% and 41%. While with the average value of DSR protocol is 94%, 95% and 92%. For throughput testing based on the number of nodes, package size and node speed is higher than the FSR protocol with an average value of 0.13 kbps, 0.20 kbps and 0.098 kbps while with an average value the DSR protocol is 0.23 kbps, 0.44 kbps and 0.87 kbps.